Avaliação do impacto ambiental do destino final do lodo de fossas sépticas nas estações de tratamento de esgotos na ETE São Cristóvão, Fortaleza-CE - Vilarouca, Jaiana da Silva (2013)
A great problem faced in big cities is the destination of the sludge generated by the pit septic tanks used by part of the population that is not served by public sewage collection. In Fortaleza Stations Sewage Treatment receiving sludge were not designed for that purpose, these ETES not endure for long the increased organic load and some already have low efficiency of treatment besides disorder caused by bad odor in the populated areas of the surroundings. This research aimed to evaluate the environmental impacts caused by in the ETE São Cristóvão that began receiving sludge pit in July 2009. To identify the impacts that ETE occasions, initially we used the method Ad hoc, soon after it was applied two questionnaires (the operator of ETE and the community). These formed the basis for further development of a checklist. To identify impacts on the receiving water body that receives the effluent from the station and for determining the efficiency of the station were evaluated physico-chemical and biological performed by CAGECE, in which were observed some parameters outside the limit of the Ordinance of SEMACE Nº 154/2002 as SST (Total Suspended Solids), Ammonia, Sulfide and Escherichia coli. Finally these impacts were analyzed by qualitative approaches probabilistic and diffuse. Was built a matrix with 36 impacts and identification of impacts was considered the hypothesis of an impact affecting more than one medium. In the middle Biotic identified two impacts both negative valuation in the middle abiotic were all negative impacts listed twelve and in the middle anthropic ,the most impacted, were thirty-one impacts, in which five positive and twenty-six negative.In this matrix there is a predominance of negative impacts.Among the aspects (effluent and sludge) treated in sludge season (with 97.82%) is the most impressive and among the steps of the wastewater treatment and sludge, the final destination is most impactful for both.When analyzing the means (biotic, abiotic and anthropic). Was observed that in order of increasing biotic and abiotic impacts in the same proportion and with 100% anthropic with 68%. After application of environmental measures various environmental impacts were mitigated, the case examples above are respectively the economy in the anthropic environment and the fauna and flora in the biotic.The environmental risk of ETE São Cristóvão is approximately 71.59% and after application of environmental measures would reduce to 40.32%.